The Role of Music in European Integration. Conciliating Eurocentrism and Multiculturalism - Riethmüller, Albrecht (Discourses on Intellectual Europe, 2017)
The volume focuses on music during the process of European integration since the Second World War. Often music in Europe is defined by its relation to the concept of Occidentalism (Musik im Abendland western music). The emphasis here turns rather to recent manifestations of its evolvement in ensembles, events, musical organisations and ideas questions of unity and diversity from Bergen to Tel Aviv, from Lisbon to Baku and deals with the tension between local, regional and national music within the larger confluence of European music. The status of classical and avante-garde music, and to a degree rock and pop, during Europe's development the past sixty years are also reviewed within the context of eurocentrism &#8211 the domination of European music within world music, a term propagated by anthropologists and ethnomusicologists several decades ago and based on multiculturalism. Conversely, the search for a musical European identity and the ways in which this search has in turn been influenced by multiculturalism is an ongoing, dynamic process.